The adoption of social media by small and medium enterprise: a systematic literature review - Ahmed Abdullah Alhamami; Noor Azuan Hashim; Roshayati Abdul Hamid; Siti Ngayesah Ab. Hamid (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
Social media (SM) has become a necessity and a method to confront challenges and fierce competition. More than half of the population are using SM. However, its implication for small and medium enterprises (SMEs) is not well documented and researched. Therefore, the purpose of this study is to review the literature pertaining to the adoption of SM by SMEs. A systematic literature review was conducted using specific keywords and database. This has resulted in reviewing 28 related articles. The findings was presented using frequency analysis. Number of articles are increasing steadily especially in emerging markets with large number of studies deploying the exploratory nature. The most widely used theory is the technological-organizational-environmental framework (TOE) and the sample size of the reviewed studies is adequate. Increasingly the structural equation modelling are being used. However, the use of intervening variable is minimal. The finding also showed that organizational and environmental context variables are the most important predictors of SM adoption by SMEs while the consequence of this adoption on business performance is mixed. There is a need for more studies to discover the consequence of adopting SM by SMEs using a combination of theories.